Brand Image Analysis Of Bank Syariah Through The Implementation Of Green Banking In Generation Z In Jatinangor: (CASE STUDY OF SMAS DARUL FATWA) - Irni Sri Cahyanti; Siti Amanah Nur Rohmah (Institut Agama Islam Negeri Kerinci, 2026)
The global climate crisis has encouraged the banking sector to implement more environmentally friendly practices, one of which is through green banking. In the context of Islamic banking, green banking is relevant because it is in line with the principles of maqasid asy-sharia. The form of implementation of Islamic banks, such as the digitization of services that have been carried out by Bank Muamalat and Bank Syariah Indonesia (BSI). However, the implementation still faces challenges such as low environmental literacy and disruption of digital systems. On the other hand, brand image is an important factor that shapes public perception of Islamic banks, especially among Generation Z who are known to be critical, environmentally friendly, and technologically literate. The purpose of this study is to analyze the influence of green banking implementation on the brand image of Sharia Banks in Generation Z at SMAS Darul Fatwa Jatinangor. The number of samples in this study was 105 respondents using a quantitative approach. The data collection technique used questionnaires. The results of this study show that the value of sig. 0.000 < 0.05 and the t-calculated value of 7.559 > t-table 1.659. The value of the determination coefficient (R2) is 0.357, meaning that 35.7% of the variation in brand image can be explained by the practice of green banking. This study implies that the implementation of good green banking can improve the brand image of Sharia Bank in the eyes of generation Z in Jatinangor District.